The Evolution of Authoring Tools Technology: An Analysis of Developments from Conventional Interactive Platforms to Artificial Intelligence-Based Systems (2015–2023) - Handini Handini; Heni Yulianti; Alpina Pebrianti; Gunawan Gunawan; Nina Nisrina (Indonesian, 2024)
The development of technology in education has driven the transformation of learning media from conventional platforms to Artificial Intelligence (AI)-based systems. This study aims to analyze the evolution of authoring tools technology in physics education from 2015 to 2023. The method employed was a literature review, examining various studies related to the development of technology-based learning media, ranging from e-learning, interactive animation, and augmented reality, to AI. The results of the study indicated that authoring tools technology has experienced significant advancement, moving from the use of simple media such as PowerPoint and Macromedia Flash toward mobile learning platforms, e-learning LMS, as well as AI-based technology and digital literacy. Each development has contributed to enhancing students' conceptual understanding, engagement, and critical thinking skills. However, challenges such as limited access to technology and user readiness still persist. Therefore, proper technology integration and the improvement of educators' digital competencies are required to utilize authoring tools optimally.